2001
DOI: 10.1200/jco.2001.19.18.3836
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Interleukin-12 on the Immune Response to a Multipeptide Vaccine for Resected Metastatic Melanoma

Abstract: These data suggest a significant proportion of patients with resected melanoma mount an antigen-specific immune response against a peptide vaccine and indicate that IL-12 may increase the immune response and supporting further development of IL-12 as a vaccine adjuvant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
103
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(105 citation statements)
references
References 49 publications
0
103
0
2
Order By: Relevance
“…Indeed, Weber et al (52) have recently shown that including IL-12 upon immunization of melanoma patients with peptides from gp100 and tyrosinase significantly increased the numbers of Ag-specific tetramer-positive and IFN-␥-producing cells in peripheral blood. We have obtained preliminary results suggesting that such immunization can significantly reduce growth of established, progressing tumors in a murine model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Weber et al (52) have recently shown that including IL-12 upon immunization of melanoma patients with peptides from gp100 and tyrosinase significantly increased the numbers of Ag-specific tetramer-positive and IFN-␥-producing cells in peripheral blood. We have obtained preliminary results suggesting that such immunization can significantly reduce growth of established, progressing tumors in a murine model.…”
Section: Discussionmentioning
confidence: 99%
“…1c). However, treatment of tumor-injected SJL mice with IL-12 failed to inhibit tumor growth, perhaps due to its known toxicity (31,32). On the basis of these results, we opted not to pursue the use of IL-12 in vivo, by either ectopic gene expression or pharmaceutical agent, to inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,55,62,63,65,67,68 The timing, dose, and location of IL -12 administration have been shown to have immunostimulatory, 22,44,67,68 immune -suppressive, 30,31,62 -65 and antiangiogenic 25,57 effects in different models. Therefore, its effect as a vaccine adjuvant should be carefully studied and used with caution, as it may in fact inhibit instead of potentiating vaccines.…”
Section: Discussionmentioning
confidence: 99%